Análise das propriedades da madeira Açoitá Cavalo - Luehea Divaricata para projetos de estruturas em madeira - Kaminski, Eduarda Dombrowski (2022)
Due to the concern with the use of renewable resources in wood, it has been compensated for its application in civil construction. To use this material, it is necessary to know its characteristics and properties for each one of them, in order to allow a wood to be used in structures. Thus, the present work has the feasibility of analyzing the Açoitá Cavalo wood structurally in civil construction. From the laboratory tests following ABNT NBR 7190: 1997, the wood became with an apparent density of 649.1 kg/m³, lower than most of the cataloged woods, and can be considered light. Regarding the compression parallel to the fibers, their results provided satisfactory values, with a final value of 57.6 MPa, exhibiting superior strength to heavier woods and over 50% of cataloged woods. As for the tensile strength, its analysis value resulted in 31.95 MPa, which compared to the reference values is lower than the cataloged specifications. It was possible to apply the wood in a construction model previously developed through adaptations of extension of initial dimensions. Even with the adaptations for the sizing, the use of wood in a lattice roof project, provided a consumption index of 0.034 m³/m², a value very close to similar projects, which indicates a good applicability for structural purposes. In the financial aspect, the wood exhibited a reduction rate of 14.06% compared to the initial dimensioning proposal, if of financial value.